2015
DOI: 10.21608/jppp.2015.75784
|View full text |Cite
|
Sign up to set email alerts
|

BIOLOGICAL ASPECTS AND THERMAL REQUIREMENTS OF THE BIRD CHERRY-OAT APHID, Rhopalosiphum padi (LINNAEUS), REARED ON WHEAT SEEDLINGS

Abstract: The bird cherry-oat aphid, Rhopalosiphum padi (Linnaeus) was studied at 15, 20 and 25 o C constant temperatures. Wheat seedlings were offered for feeding and maintaining the aphid, R. padi using the Punctured Ependorf Tube Technique. R. padi showed the longest life cycle duration at 15 o C as 12.77±1.71days. This duration decreased to 8.36±0.79 and 6.74±0.56 at 20 and 25 o C, respectively. The fecundity rate was the lowest (35.41 progenies/female) at 25 o C. It was higher at both 15 and 20 o C as 50.2 and 53.4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 9 publications
1
0
0
Order By: Relevance
“…On the other hand, the lowest developmental time was recorded when aphid reared on Misr-2 variety (4.75 days) followed insignificantly by Suhag-5 variety. Similar trend was recorded for total developmental time of nymphal stage (6.74±0.56 days) of R. padi which was reared on wheat at 25 C° by El-Fatih et al (2015). On the other hand, Taheri et al (2010) investigated the nymphal stages durations of R. padi on six wheat varieties they indicated that the six examined wheat varieties differed significantly.…”
Section: Developmental Times Of Immature Stagesupporting
confidence: 74%
“…On the other hand, the lowest developmental time was recorded when aphid reared on Misr-2 variety (4.75 days) followed insignificantly by Suhag-5 variety. Similar trend was recorded for total developmental time of nymphal stage (6.74±0.56 days) of R. padi which was reared on wheat at 25 C° by El-Fatih et al (2015). On the other hand, Taheri et al (2010) investigated the nymphal stages durations of R. padi on six wheat varieties they indicated that the six examined wheat varieties differed significantly.…”
Section: Developmental Times Of Immature Stagesupporting
confidence: 74%